Pengaruh Lingkungan Kerja, Budaya Kerja, dan Beban Kerja Terhadap Kinerja Karyawan - Jodie Firjatullah; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research has the objective of analyzing the relationship between the work environment, work culture and workload related to employee performance in an agency or company. This research uses quantitative methods through descriptive analysis, as well as online data collection using the Microsoft Forms Platform with a Likert scale of 1 to 5 with the Purposive Sampling method, there are 57 respondents with the age criteria 18-30 and currently working. Processed using the SmartPLS 4.0.9.2 application program. with Structural Eqution Modeling (SEM). The results showed that, the work environment is influential in supporting or improving the performance of its employees for the better and can produce quality work done by its employees. The work environment can be maximized when a company can implement or create a conducive, collaborative environment, and pay attention to all aspects such as the physical and psychological of its employees. Such factors as sufficient facilities, social support, and job security can increase employee performance productivity. Organizational work culture also plays an important role in shaping employee performance. Organizations with a culture that encourages innovation, collaboration, and employee motivation have better performance. Conversely, a work culture that does not support employees can hinder employee performance. Workload in accordance with individual capacity also affects employee performance. Too high a workload can lead to excessive stress and fatigue, which negatively impacts productivity. Therefore, wise management in determining workload is essential. From this study, it can be concluded that a good work environment, positive work culture, and workload adjustment can significantly improve employee performance. A company or an agency needs to pay attention to these factors to achieve optimal productivity and job satisfaction in the midst of intense competition between agencies.